LITERARY CONTRIBUTIONS IN THE MAGAZINE BRATSTVO (Heritage, 2025)
The magazine Bratstvo was published in Sarajevo from 1925 to 1941, as a spiritual magazine for religious and popular education. Although it primarily dealt with religion, it also followed the cultural life of the Serbian people in Bosnia and Herzegovina and fostered beautiful literature. Therefore, it represents a significant treasury of quality literary texts written in the spirit of the Serbian Orthodox faith and folk tradition. They celebrate the greatest Christian holidays, Christmas and Easter, and the customs that go with them. Prose contributions are written in various forms, so we have: hagiographies, biographies, letters, short stories, contributions on literature in general and notes on writers and books. The most valuable prose literary works in the magazine Bratstvo from Serbian medieval literature are biographies. In terms of the number of published prose contributions, biographies of church and secular figures are at the forefront, and biographies of heroes and dukes who became famous for their heroism in the First and Second Serbian Uprisings, and who were at the same time spiritual representatives of the Serbian people, are also represented. Bishop Nikolaj Velimirović (1881−1956) published seven prose contributions in the form of letters that were reprinted from the work Missionary Letters. A large number of prose contributions consist of moral-instructive and religious stories in which Christian virtues are emphasized and envy and anger are condemned. In choosing such content, the editor seriously thought about the education of children and youth in the spirit of the Christian faith and folk tradition. By selecting high-quality literary texts, reviews and recommendations of certain books by prominent Serbian writers and theologians, the editor influenced the formation of the audience's reading taste. By paying attention only to texts in the field of literature, one should not ignore the fact that the magazine Bratstvo, given its long existence, was a treasure trove of information from the spiritual and cultural life of its time and that it significantly influenced the raising of the level of knowledge and education in Bosnia and Herzegovina.
Keywords: Bratstvo, literary contributions, spiritual periodicals in Bosnia and Herzegovina, religious and public education.